An Analysis of The Impact of Technology on Transparency and Accountability in Financial Management in The Digital Age - Rahmah Nur Aqilah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of digital technologies has transformed financial management practices by reshaping governance structures, monitoring mechanisms, and accountability systems across public and private organizations. This study examines the impact of technology on transparency and accountability in financial management within the context of the digital age through a qualitative literature review approach. Relevant scholarly publications published between 2021 and 2026 were systematically identified and analyzed using qualitative content analysis and thematic synthesis. The findings indicate that digital technologies, including electronic government systems, blockchain, artificial intelligence, big data analytics, and integrated financial platforms, contribute significantly to improving information accessibility, strengthening financial oversight, enhancing auditability, and supporting governance effectiveness. The analysis further reveals that technology driven accountability mechanisms facilitate continuous monitoring, risk detection, compliance management, and institutional control through automated and data driven processes. Despite these benefits, several challenges remain, including cybersecurity vulnerabilities, algorithmic opacity, regulatory uncertainty, digital capability disparities, and emerging governance complexities associated with virtual economies. The study proposes a conceptual framework linking technology adoption, governance capacity, accountability, institutional trust, and sustainable financial governance. The framework highlights the importance of balancing technological innovation with governance readiness to achieve resilient, accountable, and sustainable financial management in increasingly digital environments.